Inside-out: exploring prison culture - Morittu, Alessia (Form@re - Open Journal per la formazione in rete, 2024)
Prison culture encompasses the unwritten rules, values, behaviors, and power structures within correctional institutions, emerges from interactions among inmates, staff, and the broader societal context. This culture encompasses social hierarchies, unwritten behavioral codes, survival mechanisms, and attitudes towards correctional systems. Its influence extends to inmates’ behavior, perceptions, psychological well-being, and the dynamics of prison management. Studying prison culture is vital for identifying institutional gaps, enhancing safety and efficiency, supporting inmate rehabilitation, safeguarding human rights, and informing evidence-based criminal justice policies. This chapter examines the historical evolution of prison culture from the 1800s to today, exploring its elements, effects, and the challenges it poses. By analyzing these aspects, the chapter aims to foster a comprehensive understanding to guide humane and effective corrections practices. Inside-out: esplorare la cultura carceraria. La cultura carceraria comprende le regole non scritte, i valori, i comportamenti e le strutture di potere all’interno delle istituzioni correttive, e nasce dalle interazioni tra detenuti, personale e il contesto sociale più ampio. Questa cultura include gerarchie sociali, codici comportamentali non scritti, meccanismi di sopravvivenza e atteggiamenti nei confronti dei sistemi correttivi. La sua influenza si estende al comportamento dei detenuti, alle loro percezioni, al benessere psicologico e alle dinamiche della gestione carceraria. Studiare la cultura carceraria è fondamentale per identificare lacune istituzionali, migliorare la sicurezza e l’efficienza, supportare la riabilitazione dei detenuti, tutelare i diritti umani e informare politiche di giustizia penale basate su dati concreti. Questo capitolo esamina l’evoluzione storica della cultura carceraria dal 1800 a oggi, esplorandone gli elementi, gli effetti e le sfide che pone. Analizzando questi aspetti, il capitolo mira a promuovere una comprensione approfondita per guidare pratiche correttive umane ed efficaci.